2009
DOI: 10.1021/jp810977w
|View full text |Cite
|
Sign up to set email alerts
|

SiO2−P2O5−CaO Glasses and Glass-Ceramics with and without ZnO: Relationships among Composition, Microstructure, and Bioactivity

Abstract: Bioactive glasses and glass-ceramics of the system SiO 2 -P 2 O 5 -CaO with and without zinc were synthesized by sol-gel with the aim to address the influence of both the chemical composition and the microstructure on the growth of hydroxycarbonate apatite (HCA) following soaking in simulated body fluid (SBF). In the standard compositions 58S, 70S, and 80S the silica precursor was also partially replaced with a nanoscale silica powder (HiSil) in order to separate the contributions of porosity and composition. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
42
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 22 publications
7
42
0
Order By: Relevance
“…In detail, the presence of zinc clearly increased the HCA formation rate upon immersion in SBF; this increase was proportional to the zinc content (see Fig. 1, redrawn from Bini et al (2009). As expected, silica did not show any bioactivity.…”
Section: Discussionsupporting
confidence: 58%
See 4 more Smart Citations
“…In detail, the presence of zinc clearly increased the HCA formation rate upon immersion in SBF; this increase was proportional to the zinc content (see Fig. 1, redrawn from Bini et al (2009). As expected, silica did not show any bioactivity.…”
Section: Discussionsupporting
confidence: 58%
“…In a previous study we reported preliminary evidence that a good balance between activity and toxicity, at least in vitro, can be obtained by means of carefully controlling the zinc content (Bini et al, 2009). In detail, the presence of zinc clearly increased the HCA formation rate upon immersion in SBF; this increase was proportional to the zinc content (see Fig.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations